Charge attachment induced transport – bulk and grain boundary diffusion of potassium in PrMnO3. Issue 15 (7th March 2017) - Martin, Johannes; Gräf, Melanie; Kramer, Thilo; Jooss, Christian; Choe, Min-Ju; Thornton, Katsuyo; Weitzel, Karl-Michael
Abstract : An illustration of the diffusion of potassium through the bulk and along the grain boundaries of PMO. Abstract : The transport of potassium through praseodymium-manganese oxide (PrMnO3 ; PMO) has been investigated by means of the charge attachment induced transport (CAIT) technique. To this end, potassium ions have been attached to the front side of a 250 nm thick sample of PMO. The majority of the potassium ions become neutralized at the surface of the PMO, while some of the potassium ions diffuse through. Ex situ analysis of the sample by time-of-flight secondary ion mass spectrometry (ToF-SIMS) reveals pronounced concentration profiles of the potassium, which is indicative of diffusion. Two diffusion coefficients have been obtained, namely, the bulk diffusion coefficient and the diffusion coefficient associated with the grain boundaries. The latter conclusion is supported by transmission electron microscopy of thin lamella cut out from the sample, which reveals twin grain boundaries reaching throughout the entire sample as well as model calculations.